Complications of Pediatric Tonsillectomies at Divisional Headquarter Teaching Hospital Kohat: Descriptive Case Series Study - Ikram, Muhammad Aimen; Afridi, Muhammad Saleem; Farzoq, Arshad; ., Zubair; Ullah, Ihtesham; Sajjad, Wasim (Biological and Clinical Sciences Research Journal, 2025)
Tonsillectomy is a commonly performed surgical procedure in pediatric patients for recurrent tonsillitis and obstructive sleep apnea. Despite its effectiveness, postoperative complications can impact recovery and patient outcomes. Identifying the frequency and nature of these complications can aid in optimising perioperative management and reducing morbidity. Objective: This study aimed to determine the frequency of complications following pediatric tonsillectomy. Methodology: A descriptive case series was conducted at the Department of ENT, Divisional Headquarter Teaching Hospital Kohat. One hundred thirty-one pediatric patients aged 1 to 12 years who underwent tonsillectomy were included through non-probability consecutive sampling. Patients with hematological disorders, congenital anomalies, or those undergoing adenotonsillectomy were excluded. Ethical approval was obtained, and informed consent was secured from guardians. Tonsillectomy was performed using extracapsular dissection and bipolar electrocautery techniques, with postoperative follow-up on the 1st, 7th, and 15th days. Complications, including hemorrhage, respiratory distress, infection, pain, and nausea, were recorded. Results: The mean age was 6.15 ± 3.63 years, with 54.2% males. Hemorrhage occurred in 3.8% of cases. Respiratory complications affected 7.6% of children. Infection was seen in 9.2% of children. Pain was recorded in 4.6% of children. Nausea was the most frequent complication, occurring in 14.5% of children. Conclusion: Post-tonsillectomy complications vary with age. Hemorrhage (3.8%) is more frequent in older children, while respiratory complications (7.6%) affect younger ones. Infection (9.2%) is linked to shorter symptom duration, pain (4.6%) is more common in females, and nausea (14.5%) is the most frequent complication. These findings emphasise the need for enhanced postoperative monitoring and individualised management strategies to reduce morbidity.